Interval Valued Intuitionistic Fuzzy Line Graphs - V. N. Srinivasa Rao Repalle; Keneni Abera Tola; Mamo Abebe Ashebo (BMC Research Notes, 2022)
Abstract Objectives In the field of graph theory, an intuitionistic fuzzy set becomes a useful tool to handle problems related to uncertainty and impreciseness. We introduced the interval-valued intuitionistic fuzzy line graphs (IVIFLG) and explored the results related to IVIFLG. Result Some propositions and theorems related to IVIFLG are proposed and proved, which are originated from intuitionistic fuzzy graphs (IVIG). Furthermore, Isomorphism between two IVIFLGs toward their IVIFGs was determined and verified.